Análise da qualidade de vida no trabalho em operários da construção civil da cidade de Ponta Grossa, utilizando o Diagrama de Corlett e Manenica e o questionário Quality of Working Life Questionnaire – QWLQ - 78 - Hauser, Marcus William (2012)
The present study aims to evaluate the influence of symptoms of pain/discomfort in the quality of working life of construction workers in the city of Ponta Grossa, Paraná State. During data collection, two validated instruments were used, the diagram and Corlett Manenica Questionnaire and Quality of Working Life Questionnaire - QWLQ - 78. Data were analyzed by descriptive statistics and data mining, and correlated with the variables collected by the instruments and the average age of the subjects interviewed. It was found that for a sample of 95 workers, the results of the diagram and Manenica Corlett, by ANOVA test, no significant differences. For the results obtained from QWLQ - 78, in the personal, gave the highest value (65.94) and the lowest was in the professional field (56.39). In the correlation between the results of the two instruments used the value found was r = +0.12 (weak positive correlation). In the correlation values between the diagram and Corlett Manenica and mean ages of the sample the result was r = - 0,19 (weak inverse correlation) and the correlation between the mean ages and QWLQ - 78 the result was r = + 0.57 (moderate positive correlation). It is concluded that the symptoms of pain has minimal influence on the quality of work life, while the question of age has minimal influence in the presence of painful sensations, which may affect the quality in a moderate way of life at work.